Role of Cardiac Septal Occluders in the Treatment of Gastrointestinal Fistulas: A Systematic Review - Diogo Turiani Hourneaux De Moura; Alberto Baptista; Pichamol Jirapinyo; Eduardo Guimarães Hourneaux De Moura; Christopher Thompson (Korean Society of Gastrointestinal Endoscopy, 2020)
Treating gastrointestinal (GI) fistulas endoscopically is challenging owing to an established epithelial tract. The variety of endoscopic approaches is transforming endoscopy into a first-line therapy. However, many sessions are often required, with variable success rates. Owing to these limitations, the off-label use of cardiac septal occluders (CSOs) has been reported. We searched for articles related to CSOs in the MEDLINE, EMBASE, Cochrane Library, and LILACS databases and gray literature. The primary outcomes included technical success, clinical success, and safety of CSOs in GI fistula management. A total of 25,574 records were identified, and 19 studies ultimately satisfied the inclusion criteria. Technical success was achieved in all cases. Of the 22 fistulas, 77.27% had successful closure, with a mean follow-up period of 32.02 weeks. The adverse event rate was 22.72%, with no associated mortality. Univariable and multivariable regression analyses showed no significant difference in the success of closure and adverse events in relation to several variables among the subgroups. The use of CSOs appeared to be technically feasible, effective, and safe in the treatment of GI fistulas. The satisfactory results derived from this sparse literature suggest that it can be an option in the management of GI fistulas.